The Role of Specialist Doctors' Quick Response in Improving Hospital Services in the Eyes of Patients at Advent Hospital Manado - Gerald Hendriks Langingi; Purwadhi Purwadhi; Yani Restiani Widjaja (Research of Service Administration Health and Sains Healthys, 2025)
This study aims to explore in depth the patients’ perceptions of the role of rapid response from specialist doctors in improving hospital service quality, focusing on Advent Hospital Manado. The research method used is a qualitative approach with a descriptive phenomenological design, where data were collected through in-depth interviews with patients and their families who had direct interactions with specialist doctors. The results show that the speed of the doctors’ response plays a central role in shaping patients’ sense of safety, trust, and satisfaction. Slow responses often lead to emotional anxiety and negative perceptions of hospital professionalism. Determining factors such as internal communication systems, organizational flexibility, patient-centered service culture, and individual professionalism significantly influence patients’ perceptions of service quality. This research emphasizes that response speed is not merely a technical matter, but also reflects the values of empathy and moral responsibility among healthcare professionals. Therefore, an integration of adaptive hospital management systems, the utilization of information technology, and the cultivation of a responsive culture among specialist doctors are needed to enhance holistic and humanistic service quality.